Empowering Academic Writing Through AI: A Systematic Review of Benefits and Challenges Impact - Dewi, Ni Luh Putu Meka; Nazira, Arni; Yulia, Yuyun (Journal of Language and Literature Studies, 2025)
Artificial Intelligence (AI) has significantly impacted academic writing. AI-powered tools such as ChatGPT, Grammarly, and Quilbot enhance writing efficiency by providing benefits for the users. This systematic literature review analyzed 14 studies from 2019 to 2024 to examine the benefits and challenges of using AI for academic writing. From the findings, it was found that AI helps improve writing quality and efficiency (e.g, grammar correction features to help revise quickly), and accessibility (e.g, offering grammar correction, paraphrasing tools, and content generation). However, some of the studies highlight the need to be concerned about plagiarism risk due to uncritical copying of AI-generated texts, reduced creativity and critical thinking as students became over-reliant on AI suggestions, and the inaccuracy of information produced. These challenges highlight the need for ethical guidelines and responsible AI integration to balance innovation with academic integrity. Therefore, this study emphasizes the importance of collaboration among educators, students, and policymakers in developing appropriate frameworks for AI integration in the academic context, especially in academic writing.